Analisis Keanekaragaman Jenis Tumbuhan Di Hutan Adat Nenek Limo Hiang Tinggi Nenek Empat Betung Kuning Muara Air Dua, Kapupaten Kerinci, Jambi (Jurnal Hutan dan Masyarakat, 2021)
ABSTRACT: An indigenous forest is a form of natural wealth in Indonesia. Nenek Limo Hiang Tinggi Nenek Empat Betung Kuning Muara Air Dua Indigenous Forest serves to provide a long-term guarantee of water availability, protect rural soil fertility and biodiversity, and help to secure the TNKS core zone. Collecting data was through vegetation analysis with a combination of transect and plot methods. the data was calculated on the importance value, diversity index, evenness index, and a description of the forest profile. The results showed that the Indigenous Forest contained 52 plant species dominated by Syzygium pycnanthum with an IVI of 59.16%. The dominance of the pole level was Santiria tomentosa 47.02%, sapling level was Santiria tomentosa by 45.89%, the seedling was Calamus marginatus with 61.53% and lower plants were dominated by Freycinetia banksii 93.43%. The highest species diversity was sapling with 3.64. Meanwhile, the highest evenness value was at the pole level with 0.80. The dominant type of Santiria tomentosa was influenced by the variables of sand, dust, clay, and H2O. Altingia excelsa affected by C and N, Styrax benzoin influenced by KCl and P2O5, Syzygium pycnanthum affected by KCl and P2O5 and Lithocarpus elegans influenced by sand, dust, clay, and H2O.